2004
DOI: 10.1109/tnsre.2004.837754
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal microstimulation generates functional movements after spinal-cord injury

Abstract: Restoring locomotion after spinal-cord injury has been a difficult problem to solve with traditional functional electrical stimulation (FES) systems. Intraspinal microstimulation (ISMS) is a novel approach to FES that takes advantage of spinal-cord locomotor circuits by stimulating in the spinal cord directly. Previous studies in spinal-cord intact cats showed near normal recruitment order, reduced fatigue, and functional, synergistic movements induced by stimulation through a few microwires implanted over a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 37 publications
5
114
1
2
Order By: Relevance
“…From their previous work on anesthetized spinal-intact animals, the extension movements appear to be directed backwards (Mushahwar et al 2002), although movements in all directions could be obtained in spinal-intact anesthetized animals through stimulation of the intermediate zone of the lumbar gray (Aoyagi et al 2004a). Thus the modularity in force pattern types seen in our results is similar to the modularity in movement direction seen with intraspinal microstimulation in other laboratories (Mushahwar et al 2002;Saigal et al 2004;Tai et al 2003) and the reaction forces to postural disturbances in natural behavior (Ting and Macpherson 2005;Torres-Oviedo et al 2006).…”
Section: Modularity In Force Patterns Evoked By Intraspinal Microstimsupporting
confidence: 80%
See 2 more Smart Citations
“…From their previous work on anesthetized spinal-intact animals, the extension movements appear to be directed backwards (Mushahwar et al 2002), although movements in all directions could be obtained in spinal-intact anesthetized animals through stimulation of the intermediate zone of the lumbar gray (Aoyagi et al 2004a). Thus the modularity in force pattern types seen in our results is similar to the modularity in movement direction seen with intraspinal microstimulation in other laboratories (Mushahwar et al 2002;Saigal et al 2004;Tai et al 2003) and the reaction forces to postural disturbances in natural behavior (Ting and Macpherson 2005;Torres-Oviedo et al 2006).…”
Section: Modularity In Force Patterns Evoked By Intraspinal Microstimsupporting
confidence: 80%
“…The authors do not make a distinction between the two types. In chronic spinal cats, Saigal et al (2004) showed caudal and rostral flexor movements in addition to weight-bearing extension. From their previous work on anesthetized spinal-intact animals, the extension movements appear to be directed backwards (Mushahwar et al 2002), although movements in all directions could be obtained in spinal-intact anesthetized animals through stimulation of the intermediate zone of the lumbar gray (Aoyagi et al 2004a).…”
Section: Modularity In Force Patterns Evoked By Intraspinal Microstimmentioning
confidence: 97%
See 1 more Smart Citation
“…Restoration of locomotion through ISMS has been pursued more aggressively. [60][61][62][63] ISMS implants in these studies typically consist of arrays of up to 16-24 platinum-iridium microwires, 30 μm in diameter implanted into the lumbar enlargement and targeting hindlimb motoneuron pools in the ventral horn of the spinal cord. ISMS is capable of selectively activating muscles depending on which electrode is stimulated 60,64 allowing for generation of specific movements and minimizing unwanted contractions of nearby muscles.…”
Section: Epidural and Intraspinal Microstimulation For Locomotionmentioning
confidence: 99%
“…Experimental models of FES systems with implantable electrical stimulators and portable microprocessors are under development [20,85]. Another emerging paradigm is intraspinal micro-stimulation (ISMS), where the spinal-cord-locomotor-circuits called Central Pattern Generators (CPG) are directly tapped for stimulation and restoration of limb movements [75]. Future work on these neural prosthetic devices is also focusing on decoding the intended motion trajectories from the cerebral motor cortex and using this signal to control the FES devices.…”
Section: Future Scopementioning
confidence: 99%